Is this the end? Resilience, ontological security, and the crisis of the liberal international order. Issue 2 (2nd April 2020) - Flockhart, Trine
ABSTRACT: The liberal international order is widely believed to be resilient because it has always had a remarkable ability to adapt in response to crisis and adversity. Today, the liberal order is clearly in crisis, and yet decisive action to adapt it is not taking place. Using insights from the resilience-thinking literature supplemented with insights from the literature on ontological security, the article seeks to understand why agents often fail to take decisive adaptive action, even when such action is clearly needed. The article develops a conceptual framework, including agent-level theorizing, to better understand agent motivation for undertaking adaptive action and a conception of the social site for resilience as an ideal-type social domain in which resilience is constituted and defined in the interaction between patterns of power, principles, and practice. The article contributes to resilience-thinking by demonstrating a plausible link between agents' ability to invoke their agency and their ontological security.